Creatures of attention : aesthetics and the subject before Kant - Wankhammer, Johannes, 1982- (Cornell University Press and Cornell University Library, 2024)
"The book examines the discourse on attention emerging in the European Enlightenment (1650-1780) with a focus on German philosophy and literature. It argues that this discourse influenced the formation of aesthetic philosophy in the eighteenth century. Notable figures discussed include René Descartes, G.W.F. Leibniz, Christian Wolff, and Alexander Baumgarten."-- Provided by publisher.
Keywords: Attention -- Philosophy.; Subjectivity.; Aesthetics, Modern -- 18th century.; Autonomy (Philosophy); Philosophy, German -- 18th century.; German literature -- 18th century -- History and criticism.; Attention -- Philosophie.; Esthétique -- 18e siècle.; Autonomie (Philosophie); Philosophie allemande -- 18e siècle.; Littérature allemande -- 18e siècle -- Histoire et critique.; PHILOSOPHY / Aesthetics; Philosophy: metaphysics & ontology.; Philosophy.; Electronic books.